Effect Of Using Industrial By Product Silage In Ration On Income Over Feed Cost (Iofc) And Feed Economic Efficiency Of Local Rabbit - husein suhada (Jurnal Sains Peternakan, 2015)
ABSTRACT  The aimed of this research was to evaluate the effect of using industrial by product on income over feed cost (IOFC) and feed economic effiency on local rabbit. Material used were 12of local rabbit,six weeks old. Industrial by product used include soybean skin, pulp, rice bran, and molasses. Industrial by product were fermentation with Cattlegro. Industrial by product silage were substitute with commercial feed. The experiment used was Block Randomized Design with 3 treatments and 4 group. The treatments were 100% complete feed (P0), 80% complete feed+20% industrial by product silage, and 60% complete feed+40% industrial by product silage. The basal feed was commercialcomplete feed produced by PT. Japfa Comfeed Indonesia. Results showed that there were significant effect (P<0.01) on using fermented industrial by product to income over feed cost (IOFC) andfeed economic efficiency on local rabbit. Average Income over feed cost (Rp/head) were 7.946,68 ;12.119,95 ; and 18.847,69respectively. Average Feed economic efficiency (Rp/head) were41.090,00 ;28.353,35 ; and 20.769,52 respectively. It could be concluded that usingfermented industrial by productdo by product could increase in income over feed cost (IOFC) and feed economic efficiency oflocal rabbit. Keywords: fermented industrial waste, Income Over Feed Cost, Feed Economic Efficiency,                          local rabbit